STUDENTS READING HABIT AND THEIR ENGLISH ACHIEVEMENT - Joshua Christopher Diets; Virginia Gabrella Sengkey (Sean Institute, 2023)
The purpose of this study was to find out the correlation between students reading habit and their English achievement. Also, this study aimed to find out the level of students reading habit, and the level of their English achievement. An adapted questionnaire from Wardani (2019) was distributed to the 10th graders of a private high school in North Sulawesi to find out the level of their reading habits, and the data of their final grade was taken to find out their level of English achievement. Descriptive analysis of mean and Pearson Product Coefficient Correlation were used to answer the research questions. The results showed that: (1) the level of students reading habit was 2.76, which means they have moderate reading habit, (2) the level of their English achievement was 86.09, which means they have good English achievement, and (3) the p = .331 and r = .109 which indicates that there is no significant correlation between students reading habit and their English achievement; however, the correlation was found to be positive but only weak. The researchers concluded that reading habit is not a significant factor that has a relationship with students English achievement. It is recommended that future researchers or teachers can try to identify other factors that have a significant relationship with the students English achievement.